2005
DOI: 10.1002/art.20878
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular death in rheumatoid arthritis: A population‐based study

Abstract: Objective. To determine whether systemic inflammation confers any additional risk for cardiovascular death among patients with rheumatoid arthritis (RA), after adjusting for traditional cardiovascular risk factors and comorbidities.Methods. Using the population-based data resources of the Rochester Epidemiology Project, we assembled an incidence cohort of all Rochester, Minnesota residents ages >18 years who first fulfilled the American College of Rheumatology 1987 criteria for RA between January 1, 1955 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
532
3
64

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 847 publications
(641 citation statements)
references
References 65 publications
31
532
3
64
Order By: Relevance
“…Both previous studies that examined the association between smoking and CVD mortality failed to find a significant association 25, 26. In the study from the Mayo clinic 26, current smokers had double the risk of cardiovascular death compared to never smokers, although this finding did not reach statistical significance (HR 1.98 [95% CI 0.93, 4.24]), perhaps because the study was underpowered (603 patients).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Both previous studies that examined the association between smoking and CVD mortality failed to find a significant association 25, 26. In the study from the Mayo clinic 26, current smokers had double the risk of cardiovascular death compared to never smokers, although this finding did not reach statistical significance (HR 1.98 [95% CI 0.93, 4.24]), perhaps because the study was underpowered (603 patients).…”
Section: Discussionmentioning
confidence: 84%
“…In the study from the Mayo clinic 26, current smokers had double the risk of cardiovascular death compared to never smokers, although this finding did not reach statistical significance (HR 1.98 [95% CI 0.93, 4.24]), perhaps because the study was underpowered (603 patients). We did not find a significant association between current smoking and deaths due to all‐site cancer but found a strong association between current smoking and deaths due to lung cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported that patients with RA exhibit a doubled risk of myocardial infarction and 60% increased risk of cardiovascular mortality compared with the general population 42. An increased prevalence of traditional risk factors, such as diabetes mellitus, hypertension, obesity, smoking, and physical inactivity, may explain, in part, this excess cardiovascular risk in RA 8, 11.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of a previously described retrospective population-based incidence cohort of adult RA patients ages Ն18 years residing in Rochester, Minnesota, between January 1, 1955 and January 1, 1995 (15)(16)(17). The RA incidence date was defined as the date on which the subject first fulfilled the American College of Rheumatology (ACR; formerly, the American Rheumatism Association) classification criteria (24).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with RA are at increased risk of CVD, including myocardial infarction (MI) and heart failure (HF), as well as CV mortality (15)(16)(17)(18)(19). Chronic inflammation that occurs in this population is believed to contribute to the increased risk (20,21).…”
mentioning
confidence: 99%